PENGARUH KUALITAS KERJA DAN MOTIVASI KERJA PEGAWAI PEMERINTAH DAERAH TERHADAP KEPUASAN MASYARAKAT KABUPATEN ACEH SINGKIL - Aldri Frinaldi; Boni Saputra; Nora Eka Putri; Jumiati Jumiati; Adil Mubarak; Lince Magriasti; Fenni Hasanah; Febri Nola Distra (Jurnal EL-RIYASAH, 2022)
Public satisfaction with public organizations is very important because of the relationship of public trust. Community satisfaction is a basic factor to determine success in a public organization. The public's bad perception of public services causes their level of satisfaction to be low. This also happens to the people of Aceh Singkil today. The purpose of the study was to examine and determine the effect of work quality and work motivation of local government employees on the satisfaction of the people of Aceh Singkil Regency. The research was conducted in Aceh Singkil Regency using an associative quantitative approach. The sampling technique used was convenience sampling (sampling based on subject availability), with a sample size of 100 respondents. Data collection uses an instrument in the form of a questionnaire which is based on variable indicators. This study consists of three variables, namely two independent variables (quality of work and work motivation) and one dependent variable (satisfaction). The previous questionnaire has been tested for validity and reliability. Data collection techniques also use documentation studies using primary data and secondary data. The data was then analyzed using multiple regression analysis after the classical assumption test was previously carried out. The results of the study concluded that there was a simultaneous positive effect of the quality of work and work motivation of local government employees on the satisfaction of the people of Aceh Singkil Regency by 39.6%, with a significant contribution. While partially each independent variable also has a significant influence on community satisfaction, namely 36.1% for the effect of the work quality variable and 26.2% for the influence of the work motivation variable.